2017
DOI: 10.1364/oe.25.008212
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on optical image encryption with asymmetric double random phase and computer-generated hologram

Abstract: Optical image encryption, especially double-random-phase-based, is of great interest in information security. In this work, we experimentally demonstrate the security and feasibility of optical image encryption with asymmetric double random phase and computer-generated hologram (CGH) by using spatial light modulator. First of all, the encrypted image modulated by asymmetric double random phase is numerically encoded into real-value CGH. Then, the encoded real-value CGH is loaded on the spatial light modulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…Holography has captivated us with its stunning visual effects, finding applications in augmented reality, medical imaging, laser multibeam projection, beam shaping, interference measurement, optical manipulation, and anticounterfeiting . By manipulating the phase or amplitude of light as it passes through the plane of the hologram, arbitrary grayscale images can be projected in the far field.…”
Section: Introductionmentioning
confidence: 99%
“…Holography has captivated us with its stunning visual effects, finding applications in augmented reality, medical imaging, laser multibeam projection, beam shaping, interference measurement, optical manipulation, and anticounterfeiting . By manipulating the phase or amplitude of light as it passes through the plane of the hologram, arbitrary grayscale images can be projected in the far field.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, optical encryption systems based on imaging mechanisms [8,14,28,29], such as ghost imaging, diffractive imaging and interferometric imaging, are illustrated to be applicable for securing information. It is also found that computer-generated hologram (CGH) [30][31][32][33][34][35] can be applied for optical encryption, and its remarkable advantages, e.g., simple implementations, have been explored for practical applications. In the CGH-based optical encryption, the input image can be iteratively or non-iteratively encoded into one or several phase-only masks (i.e., CGH) [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…To improve its security, the DRPE is extended to different domains such as fractional Fourier domain [9], Fresnel domain [10], Gyrator domain [11], and Hartley domain [12]. Other strategies, such as interference-based encryption [13]- [15], computer-generated hologram-based optical encryption [16], [17], and computational ghost image encryption [18]- [21] have also been proposed for higher security encryption. With the emergence of cryptanalysis of cryptosystems, researchers have successively proposed asymmetric encryption approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the asymmetric cryptosystems show resistance to various attacks on account of the existence of private key and public key. Subsequently, researchers successively propose improved asymmetric cryptosystems [17], [30]- [37] due to its significant asymmetric characteristics.…”
Section: Introductionmentioning
confidence: 99%